GRID-DL – SEMANTIC GRID INFORMATION SERVICE - Pospishniy, Oleksandr; Stirenko, Sergiy (International Journal of Computing, 2011)
The effectiveness of complex Grid systems strongly depends on the availability, accuracy and relevance of information on all connected resources, their characteristics and state. An access to this information plays a very im- portant role in any Grid system, providing necessary information for other Grid components and users. We believe that application of semantic technologies can improve Grid utilization and enhance user interaction with the system. We present our vision of the semantic Grid resource information service.